Identifying patients with cerebral infarction within the time window compatible with reperfusion therapy, diagnostic performance of glutathione S-transferase-π (GST-π) and peroxiredoxin 1 (PRDX1): exploratory prospective multicentre study FLAG-1 protocol - Nicolas Girerd; Arif Karakus; Jean-Charles Sanchez; Sophie Marchal; Anne Aubertin; Sanae Bouali; Kevin Duarte; Sandrine Reymond (BMJ Open)
Introduction Plasma biomarkers may be useful in diagnosing acute cerebral infarction requiring urgent reperfusion, but their performance remains to be confirmed. If confirmed, these molecules could be used to develop rapid and reliable decentralised measurement methods, making it possible to initiate reperfusion therapy before hospital admission. The FLAG-1 large prospective study will constitute a plasma bank to assess the diagnostic performance of two biomarkers: glutathione S-transferase-π and peroxiredoxin 1. These molecules are involved in the oxidative stress response and could identify cerebral infarction within a therapeutic window of less than 4.5 hours following the onset of symptoms. Secondary objectives include assessing performance of these biomarkers within 3-hour and 6-hour windows; identifying additional biomarkers diagnosing cerebral infarction and significant criteria guiding therapeutic decisions: ischaemic features of stroke, presence of diffusion/fluid-attenuated inversion recovery mismatch, volume of cerebral infarction and penumbra on cerebral MRI.Methods and analysis The exploratory, prospective, multicentre FLAG-1 Study will include 945 patients with acute stroke symptoms (onset ≤12 hours, National Institute of Health Stroke Scale score ≥3). Each patient’s 25 mL blood sample will be associated with cerebral MRI data. Two patient groups will be defined based on the time of blood collection (before and after 4.5 hours following onset). Receiver operating characteristic analysis will determine the diagnostic performance of each biomarker, alone or in combination, for the identification of cerebral infarction <4.5 hours.Ethics and dissemination The protocol has been approved by an independent ethics committee. Biological samples are retained in line with best practices and procedures, in accordance with French legislation. Anonymised data and cerebral imaging records are stored using electronic case report forms and a secure server, respectively, registered with the French Data Protection Authority (Commission Nationale de l'Informatique et des Libertés (CNIL)). Results will be disseminated through scientific meetings and publication in peer-reviewed medical journals.Trial registration number ClinicalTrials.gov Registry (NCT03364296).